Saint Maelrubha: his History and Churches (Proceedings of the Society of Antiquaries of Scotland, 1862)
This article presents the family history and ecclesiastical career of Saint Maelrubha, who founded the monastery at Applecross in Ross-shire. The author notes that there are significant differences between the Irish and Scottish sources in regards to the events of this saint's life, as well as in the spelling of his name and the date of his feast day. The second part of the article discusses some of the locations and families that may have been associated with Saint Maelrubha.